2016
DOI: 10.4038/tare.v19i3-4.5357
|View full text |Cite
|
Sign up to set email alerts
|

Effect of good governance perception towards job satisfaction: a case study of the agriculture professionals attached to the Department of Agriculture Sri Lanka

Abstract: Effectiveness of service delivery system of public sector organizations like Department of Agriculture (DoA) depends on the job satisfaction of the relevant officers. Research Officers (ROs), Agriculture Officers (AOs), Lecturers (LCs) and Subject Matter Specialists (SMSs) are the key officers in the DoA in Sri Lanka Agriculture Service (SLAgS). It is therefore, a pre requisite to improve the job satisfaction of SLAgS officers in the DoA in order to improve the effectiveness of service delivery system. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The study also found that setting a good governance system is necessary to derive good employees' behavior. (Sandika, et al, 2016) also concluded that there is a positive and significant relationship between job satisfaction and employees' awareness of good governance at the Sri Lankan Ministry of Agriculture. The study found that the perception of good governance by the respondents led to an increase in their level of job satisfaction.…”
Section: The Relation Between Good Governance and Job Satisfactionmentioning
confidence: 99%
“…The study also found that setting a good governance system is necessary to derive good employees' behavior. (Sandika, et al, 2016) also concluded that there is a positive and significant relationship between job satisfaction and employees' awareness of good governance at the Sri Lankan Ministry of Agriculture. The study found that the perception of good governance by the respondents led to an increase in their level of job satisfaction.…”
Section: The Relation Between Good Governance and Job Satisfactionmentioning
confidence: 99%